2014
DOI: 10.1021/ma500236z
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Changes in Crystalline Structures of Polyimides Analyzed by Wide-Angle X-ray Diffraction at High Pressures

Abstract: Variations in the crystalline structures of polyimides (PIs) were analyzed under high pressures up to 8 GPa using wide-angle X-ray diffraction. The compressibilities along the polymer chain axis (c-axis) of rigid-rod PIs increased with an increase in the number of phenyl rings in the diamine moiety (PMDA/PPD < PMDA/BZ < PMDA/DATP). This could be due to an increased shrinkage of the C−C bond lengths between the phenyl rings and/or a pressure-induced deformation of the periodic structure associated with changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…The chemical composition and crystalline structure of the resulting PIs were confi rmed through Fourier transform infrared spectroscopy (FTIR) spectroscopy (Figure S1a, Supporting Information) and X-ray powder diffraction (XRD) ( Figure S1b, Supporting Information). [ 25,26 ] Scanning electron microscopy (SEM) images showed that the samples prepared using DMF or NMP clearly exhibited different 3D hierarchical architectures, although they were constructed by 2D nanosheets ( Figure 2 ). Among them, the In the last decade, 3D carbon superstructures (CSSs) constructed from the assembly of low-dimensional segments such as carbon nanotubes or graphene sheets, have attracted increasing interest.…”
Section: Doi: 101002/adma201505131mentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition and crystalline structure of the resulting PIs were confi rmed through Fourier transform infrared spectroscopy (FTIR) spectroscopy (Figure S1a, Supporting Information) and X-ray powder diffraction (XRD) ( Figure S1b, Supporting Information). [ 25,26 ] Scanning electron microscopy (SEM) images showed that the samples prepared using DMF or NMP clearly exhibited different 3D hierarchical architectures, although they were constructed by 2D nanosheets ( Figure 2 ). Among them, the In the last decade, 3D carbon superstructures (CSSs) constructed from the assembly of low-dimensional segments such as carbon nanotubes or graphene sheets, have attracted increasing interest.…”
Section: Doi: 101002/adma201505131mentioning
confidence: 99%
“…Based on these results, we propose a pressure-induced, concentration-dependent hierarchical self-assembly mechanism for explaining the formation of PI nanosheets and their assembly into 3D superstructures: Under solvothermal reaction conditions, a high temperature facilitates the dehydration of polyamic acid, and high pressure induces the crystallization of the resultant PI. [ 26,29 ] As shown in Figure 1 , the folding of a 1D linear PI chain with strong intermolecular forces fi rst induced the formation of fl at nanosheets, which further organized into 3D assemblies with various morphologies depending on the polyamic acid concentration. The hierarchical self-assembly mechanism of PI is highly similar to the growth of the lamellar structures and spherulites of polymers ( Figure S4, Supporting Information), [18][19][20][21] in which the diluted solution of polyamic acid tends to form lamellar structures through molecular chains orienting perpendicularly to the nanosheet surface.…”
Section: Doi: 101002/adma201505131mentioning
confidence: 99%
“…These studies were augmented by structural high pressure studies of polyphenylenes by Heimel et al and Gitsas et al, and by optical high pressure studies including studies of poly( p‐ phenylene vinylene) by Morandi et al and investigations of fluorene copolymers by Schmidtke et al Common to all these studies are planarization of otherwise twisted polymers followed by a redshift in photoluminescence (PL). Also, there are structural high pressure studies of oligoacenes and related molecules including fluorene as well as of related hairy rod type polymers like polyimides, which show diverse structural transitions and dependencies between the effect of pressure and side chain structure.…”
Section: Introductionmentioning
confidence: 99%
“…For the PMDA–PIs, it should be noted that PMDA–DCHM, which possesses two cyclohexyl rings with a bent CH 2  linkage, exhibited a large K p (0.635) compared with the PIs with linear structures (0.603–0.613). This should have resulted from the ordered structures in PMDA–DCHM, which was characterized by wide‐angle X‐ray diffraction in our previous study . A sharp peak for d = 16.1 Å (002) and a broad peak for d = 5.1 Å (chain packing) were observed for this PI.…”
Section: Resultsmentioning
confidence: 53%